Pengelolaan Pelaksanaan Pembelajaran Seni BudayaDi Sma Negeri 1 Pulokulon Grobogan - Sutiyaso, Sutiyaso; , Prof. Dr. Sutama.M.Pd (2017)
The purpose of this research is to describe 1) the availability of space and the media, 2) materials and teaching materials, 3) the interaction of students in the implementation of learning art and culture in SMA N 1 Pulokulon Grobogan. This is a qualitative research, data collection techniques using documentation, interviews and observation. Data were analyzed using interactive data analysis. Results penilitian 1) management of learning space for arts and culture in accordance with the number of classes in SMA N 1 Pulokulon. To study media arts and culture has been provided by the school both music, dance and visual arts. The school also encourages the participation of students to make learning media art and culture to enrich the existing learning media. 2) Master SMA N 1 Pulokulon has a very important role in preparing materials and teaching materials appropriate to the needs and characteristics of teaching materials that will be presented. The source material and the teaching materials used in teaching art and culture in SMA N 1 Pulokulon Grobogan comes from textbooks, students' worksheet (LKS), internet and other references relevant to learning materials that will be taught as examples of artwork. 3) In the study of art and culture in SMA N 1 Pulokulon interactions that occur in two patterns of interaction that is centered on the teacher-centered content. Keywords: arts and culture, management, learning